A study on the form of distribution of the experimental value of current collector pressing on the contact wire - P. G. Tyurnin; N. V. Mironos; M. N. Emel’Yanova (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
Current collection, while electric rolling stock is running, is a complex process. The quality of dynamic interaction is estimated at an average contact pressure of current collector and its standard deviation. To measure contact pressing force special equipment is used that is installed on the current collector and provides force measurements in contact “current collector-contact wire” with the required frequency. Obtained contact pressure measurement values are random variables that are affected by many factors, each of which is not possible to take into account simultaneously. Therefore, currently the most effective way to study the contact pressing is to carry an experiment. Preliminary check of obtained experimental distribution of contact pressure for normality was determined considering the basic static distribution parameters. Coefficients of skewness and kurtosis were calculated. To determine the nature of density of the experimental data distribution a histogram, as well as theoretical and experimental graphs of distribution density were built. Probabilistic values for evaluation of law of experimental data distribution are shown. Check on plausibility of the hypothesis about the consistency of theoretical and experimental distribution density was made, applying the criterion of Pearson agreement. The study on type of distribution of experimental value of contact pressing force of the current collector on the contact wire of catenary as a random variable showed that there are deviations from the normal law. Since the cumulative probability for the range ±2σ and ± 3 of normal distribution and the cumulative probability of contact pressure in the respective ranges differ by less than 1 %, in practice, to assess the quality of current collection it is permissible to use the average contact pressing of the current collector and its standard deviation.